Ergodic Capacity for Evaluation of Mobile System Performance (Journal of Engineering, 2020)
In this research the performance of 5G mobile system is evaluated through the Ergodic capacity metric. Today, in any wireless communication system, many parameters have a significant role on system performance. Three main parameters are of concern here; the source power, number of antennas, and transmitter-receiver distance. User equipment’s (UEs) with equal and non-equal powers are used to evaluate the system performance in addition to using different antenna techniques to demonstrate the differences between SISO, MIMO, and massive MIMO. Using two mobile stations (MS) with different distances from the base station (BS), resulted in showing how using massive MIMO system will improve the performance than the standard SISO and MIMO techniques, under Rayleigh fading channel. Using MATLAB as a simulation tool it was found that the ergodic channel capacity enhance by increasing the power of the source and the base station antenna and it behaves in an opposite way with distance.